Synthesis, photolysis studies and in vitro photorelease of caged TRPV1 agonists and antagonists. - Ryssen, V; Avlonitis, N; Giniatullin, R; McDougall, C; Carr, J; Stanton-Humphreys, M; Borgström, E; Brown, C; Fayuk, D; Surin, A; Niittykoski, M; Khiroug, L; et al. (2009)
The synthesis of a range of caged TRPV1 agonists and antagonists is reported. The photolysis characteristics of these compounds, when irradiated with a 355 nm laser, have been studied and in all cases the desired compound was produced. Photolysis of a caged TRPV1 agonist in cultured trigeminal neurons produced responses that were consistent with the activation of TRPV1 receptors.